Correlação dos aspectos comportamentais com a obesidade infantil em um contexto de pandemia de Covid-19 - ELTCHECHEM, CAMILA DA LUZ (2021)
The current obesity scenario in the world has drawn attention and motivated many researchers to understand the mechanisms involved in this complex disease. In addition, the Covid-19 pandemic brought many changes to people's daily lives, and especially to children and teenagers, such as the increase in time at home and the closing of schools. Objective: To investigate the correlation of behavioral aspects with childhood obesity during the Covid-19 pandemic. Methods: Data on physical activity, sleep and time of exposure to media were obtained through the application of a questionnaire, while the Body Mass Index (BMI) was obtained through an anthropometric analysis and the nutritional status assessed through the classification table of the World Health Organization (WHO, 1995). Results: Of the 34 students who composed the study, 12 (35.3%) were overweight and 3 (8.8%) were obese. Regarding the level of physical activity during the pandemic, 1 (2.9%) reported being more active, while 24 (70.6%) reported being less active and 9 (26.4%) reported being at the same level of activity. physical activity that they performed before the pandemic. In the association of overweight children who reported being less active during the pandemic, a significance was found through Person's Chi-square test=19,802ª, with p=0.003 in this correlation. Conclusions: The Covid-19 pandemic had an impact on people's lifestyles, especially for children who experienced the indirect effect of school closings, culminating in increased exposure to screens and reduced physical activity, thus contributing to the increase of childhood overweight and obesity.